Generalized lymphadenopathy in patient with fever of unknown origin as a differential diagnostic challenge - case report - Sofija Sekulic Markovic,; Ivana Rakovic,; Sara Petrovic,; Dusica Petrovic Rodic,; Nenad Zornic,; Biljana Popovska Jovicic , (Journal of the Pakistan Medical Association, 2021)
Published in May - 2021